Emergence of Multi-Drug Resistance and Its Association With Uncommon Serotypes of Streptococcus agalactiae Isolated From Non-neonatal Patients in Thailand - Tulyaprawat, Orawan; Pharkjaksu, Sujiraphong; Shrestha, Raj Kumar; Ngamskulrungroj, Popchai (Frontiers in Microbiology, 2021)
Group B streptococcus (GBS) or Streptococcus agalactiae is an opportunistic pathogen that causes serious illness in newborns, pregnant women, and adults. However, insufficient detection methods and disease prevention programs have contributed to an increase in the incidence and fatality rates associated with this pathogen in non-neonatal patients. This study aimed to investigate factors of the increased incidence by investigation of serotype distribution, virulence factors, and antimicrobial susceptibility patterns from invasive GBS disease among non-neonatal patients in Thailand. During 2017-2018, a total of 109 S. agalactiae isolates were collected from non-pregnant patients. There were 62 males and 47 females, with an average age of 63.5, ranging from 20 – 96 years old. Serotypes were determined by latex agglutination assay and multiplex PCR-based assay. Among those isolates, 7 virulence genes (rib, bca, pavA, lmb, scpB, cylE, and cfb) were detected by polymerase chain reaction amplification, and were determined for their susceptibility to 20 antimicrobial agents using a Sensititre Streptococcus species STP6F AST plate. Among the study isolates, serotypeIII was predominant (52.3%), followed by serotypeV and serotypeVI (13.8% for each), serotypeIb (11.9%), and other serotypes (8.2%). Of the 7 virulence genes, pavA was found in 67.0%. Except for one, there were no significant differences in virulence genes between serotypeIII and non-serotypeIII. Study isolates showed an overall rate of nonsusceptibility to penicillin, the first-line antibiotic of only 0.9%, whereas the resistance rates measured in tetracycline, clindamycin, azithromycin, and erythromycin were 41.3%, 22.0%, 22.0%, and 22.0%, respectively. Strains that were resistant to all four of those drugs were significantly associated with non-serotypeIII(p<0.001). Using multi-locus sequence typing (MLST), 40.0% of the four drugs resistant isolates belonged to serotypeVI/ST1, followed by serotypeIb/ST1 (35.0%). Cluster analysis with the GBS global isolates suggested that the multiple drug-resistant isolates was highly associated with the clonal complex 1 (p<0.001). Compared to the 2014 study of 210 invasive GBS isolates conducted in 12 tertiary hospitals in Thailand, the proportion of serotypeIII has dramatically dropped from nearly 90% to about 50%. This suggests that resistances to the second-line antibiotics for GBS might be the selective pressure causing the high prevalence of non-serotypeIII isolates.